Effects of bitter almond on production performance, antioxidant capacity and immune function of Rongde black-feathered small-sized layer strain - Chen, Jun-Nan; Chen, Yi-Fan; Guo, Han; Hao, Er-Ying; Shi, Lei; Chen, Hui; Chen, Xiang-Yu; Ma, Ya-Peng; Wang, De-He; Xu, Li-Jun (Frontiers in Veterinary Science, 2025)
IntroductionBitter almond, as a natural plant-derived additive, possesses the potential to enhance antioxidant and immune functions. Furthermore, its rapid metabolism in vivo leads to low residual levels. However, its effects on laying hens’ production performance and health remain unclear.MethodsA total of 180 healthy 43-week-old Rongde black-feathered small-sized layer strain (RBSL) with similar production performance were selected and randomly divided into four groups (with five replicates per group). These groups were fed diets containing 0 (control group, CON), 0.25 (low-dose group, LBA), 0.5 (medium-dose group, MBA), and 0.75 (high-dose group, HBA) g/kg of bitter almond, respectively, for an 8-week experiment period.ResultsThe results showed that in terms of production performance. The MBA group exhibited a significantly higher laying rate, daily feed intake, and Haugh unit than the CON group (p < 0.05). The HBA group also showed greater Haugh unit and yolk color versus controls (p < 0.05). In terms of antioxidant and immune functions, the T-AOC, GSH-Px, and IgA levels in the MBA and HBA groups were significantly higher than those in the CON group (p < 0.05), while the IgM level was significantly increased only in the HBA group (p < 0.05). In terms of intestinal morphology, LBA, MBA, and HBA groups all significantly improved the intestinal morphology of RBSL, with the MBA group showing the most pronounced improvement (p < 0.05). Additionally, metabolomics analysis revealed that bitter almond powder altered plasma metabolite profiles. KEGG enrichment analysis indicated that these alterations affected pathways including ABC transporters and tumor choline metabolism (p < 0.05). Meanwhile, microbiome analysis showed that bitter almond powder modified the cecal microbial community structure, notably resulting in a significant decrease in the abundance of the genus Negativibacillus in the HBA group. Furthermore, the abundance of Negativibacillus was significantly positively correlated with levels of IgA, IgM, and GSH-Px (p < 0.05).DiscussionIn conclusion, bitter almond supplementation improves egg production, along with antioxidant and immune status, as well as intestinal microbiota. Considering comprehensive benefits and safety, 0.5 g/kg is the optimal addition dosage, which can improve production performance without showing potential toxicity risks.